(untitled) (Revista Contexto & Educação, 2026)
Reading has assumed a central position in our society, besides it is through reading that the individual insertion in various cultural and social domain may become effective. In this context, schools play a fundamental role in encouraging reading practices, particularly in the context of Technical and Professional Education (TPE), since its educational project focuses comprehensive human development. Therefore, the research project “The reader’s profile in IFFar-SVS: professional teaching and reading” aimed, in 2023, to outline technical and professional students socioeconomic and reading profiling. To achieve this goal, a questionnaire containing 31 questions, divided into 4 sections, was applied in the interest of drawing a correlaction between socioeconomic profiling, reading habits, school environment and access to books of these students. Among the results obtained, it is notorious that the average number of books read annually exceeds brazilian reading average, notwithstanding students prefer other leisure activities to reading. The proeminent genres the students indicated include books adaptated into films and works discussed in campus reading projects, a fact that highlights school environment in promoting readings as means of broaden the students sociocultural repertoire. Finally, the responses obtained from the analysis reveal relevante aspects about these young people reading habits, foretelling some possibilities and challenged that need to addressed in greater detail in school.